Circ_0006988 promotes the proliferation, metastasis and angiogenesis of non-small cell lung cancer cells by modulating miR-491-5p/MAP3K3 axis. Issue 13 (3rd July 2021) - Yang, Chao; Shi, Jiang; Wang, Jie; Hao, Dexun; An, Jinlu; Jiang, Junguang
ABSTRACT: Circular RNAs (circRNAs) are related to the progression of non-small cell lung cancer (NSCLC). However, the roles and mechanism of circ_0006988 are largely unknown. The levels of circ_0006988, Low-Density Lipoprotein Receptor Class A Domain Containing 3 (LDLRAD3), microRNA-491-5p (miR-491-5p), Mitogen-Activated Protein Kinase Kinase Kinase 3 (MAP3K3) were measured using quantitative real-time polymerase-chain reaction (qRT-PCR) and western blot assay. The characteristic of circ_0006988 was analyzed by RNase R assay and Actinomycin D assay. Functional analyses were processed by Cell Counting Kit-8 (CCK-8) assay, 5-ethynyl-2ʹ-deoxyuridine (EdU) assay, colony formation assay, flow cytometry analysis, transwell assay, wound-healing assay and tube formation assay. The interactions between circ_0006988 and miR-491-5p as well as miR-491-5p and MAP3K3 were analyzed by dual-luciferase reporter assay and RNA immunoprecipitation (RIP) assay. Murine xenograft model assay was processed to verify the function of circ_0006988 in vivo . Immunohistochemistry (IHC) assay was conducted to examine the level of Ki67. Circ_0006988 abundance was increased in NSCLC tissues and cells. Circ_0006988 silencing restrained NSCLC cell proliferation, migration, invasion and angiogenesis, and induced apoptosis. Circ_0006988 sponged miR-491-5p, which directly targeted MAP3K3. MiR-491-5p overexpression repressed NSCLC cell malignant behaviors. MiR-491-5p downregulation or MAP3K3 overexpression reversed the effect of circ_0006988 silencing on NSCLC cell progression. In addition, circ_0006988 knockdown reduced xenograft tumor growth. ssCirc_0006988 contributed to the development of NSCLC by miR-491-5p/MAP3K3 axis.